Research on Synchronization Capability of Supply Chain Network Based on Master Stability Function - Xiaodong Qian, Peng Zhang (Forest Chemicals Review, 1970)
According to the diversity of enterprises, the supply chain network is often a mixed network of multiple enterprises, and the existing research rarely involves the hierarchical type and coupling strength between enterprises, which is not conducive to the study of the influence of the relationship between enterprises on network synchronization. This paper proposes a research method of supply chain network synchronization capability, which provides a theoretical basis for supply chain network synchronization. Based on the gravitational formula to construct the coupling strength between enterprises, the degree value is defined as the mass, the serial number difference of the enterprise is distance and the industry driving coefficient is the gravitational constant; again, considering the different types of enterprises, the enterprise level difference is defined as the internal connection in the master stability function, The influence component of the matrix. The coupling strength and interconnection matrix in the master stability function are improved through two aspects, so that the research results of the master stability function can better guide the improvement of the synchronization ability of the supply chain network. The study draws the following three conclusions: 1) The comparison of the improved master stability function and the stability domain of the main stability function shows that in order to increase the stability area in the supply chain network, cross-level cooperation between enterprises should be minimized; 2) New enterprises In the development, try to avoid the choice of “the rich get richer”. This kind of cooperation among enterprises has the influence of lower availability and higher inequality in costs and terms. It will generally limit the synchronization of supply chain networks. 3) When the supply chain network topology is stable, the government can adjust the industry driving coefficient to accurately remove the synchronous enterprise relationship that requires a high price to achieve. The deficiencies of the research are mainly reflected in the fact that the industry driving coefficient is not set according to industry differences, and the setting of the influence components of the interconnection matrix only considers the impact of stratification.